Adjustment to university by students in Canada, Spain, and Ecuador: distress and identity issues - Barbara M. Gfellner; Ana I. Cordoba; Maria Fernanda Cordero-Hermida (Academia Mental Health & Well-Being)
A crisis in mental health is seen in the escalation of psychological difficulties among university students at a time in their life when they are experiencing increased challenges dealing with identity concerns. In this study, we examined the alignment of psychiatric symptoms with developmental psychopathology to clarify associations between these diverse approaches to students’ mental health. The focus is on the severity of psychiatric symptoms in conjunction with students categorized in terms of identity distress. Identity distress refers to the experience of extreme uncertainty and dysfunction related to personal identity issues that are critical during the lifespan. The Counseling Center Assessment of Psychological Symptoms (CCAPS-34) was used to assess clinical diagnoses, while the Identity Distress Scale measured upset and uncertainty related to identity issues. The outcome measure evaluated scholastic, interpersonal, and affective functioning at university. Participants included 1,704 students from Canada, Spain, and Ecuador (with a median age of 19 years). Taken together, 20.8% of the sample was classified with identity distress, 36% with moderate to severe psychological problems, and 64% were classified as flourishing, meaning that they experienced neither psychological symptoms nor serious identity difficulties. Despite differences between the countries, the predicted alignment of psychological symptom severity in relation to identity distress was supported and associated with students’ adjustment to university. The findings underscore the importance of addressing identity disturbances in conjunction with clinical diagnosis to meet the functional mental health needs of university students. The need for culturally sensitive interventions and research is emphasized.